Answer:
TRUE. We need to use the chain rule to find the derivative of the given function.
Explanation:
Chain rule to find the derivative,
We have to find the derivative of F(x)
If F(x) = f[g(x)]
Then F'(x) = f'[g(x)].g'(x)
Given function is,
y =
Here g(x) = (2x + 3)
and f[g(x)] =
![√(2x+3)](https://img.qammunity.org/2021/formulas/mathematics/college/6vz35cbeku13rc0s9r5kgkwje6q7x7b6tk.png)
![(dy)/(dx)=(d)/(dx)(√(2x+3)).(d)/(dx) (2x+3)](https://img.qammunity.org/2021/formulas/mathematics/college/2sbc668062rq46s860ola5izurc5bggdy3.png)
y' =
![(1)/(2)(2x+3)^{(1-(1)/(2))}.(2)](https://img.qammunity.org/2021/formulas/mathematics/college/3tpq0hs1eejw7f0jc7o94nvfqdh0n6qoj9.png)
=
![(2x+3)^{-(1)/(2)}](https://img.qammunity.org/2021/formulas/mathematics/college/60chnwc2qsrqfbwm0xwvsri86aek6cukh1.png)
y' =
![(1)/(√(2x+3))](https://img.qammunity.org/2021/formulas/mathematics/college/lnpcrcciu7rcinqapfr4y0cg0039437jy0.png)
Therefore, it's true that we need to use the chain rule to find the derivative of the given function.